Genetic architecture in neonatal intensive care unit patients with congenital heart defects: a retrospective study from the China Neonatal Genomes Project. Issue 3 (20th May 2022) - Wang, Huijun; Xiao, Feifan; Qian, Yanyan; Wu, Bingbing; Dong, Xinran; Lu, Yulan; Cheng, Guoqiang; Wang, Laishuan; Yan, Kai; Yang, Lin; Chen, Liping; Kang, Wenqing; et al.
Abstract : Background: Congenital heart defects (CHDs) are the most common type of birth defects. The genetic aetiology of CHD is complex and incompletely understood. The overall distribution of genetic causes in patients with CHD from neonatal intensive care units (NICUs) needs to be studied. Methods: CHD cases were extracted from the China Neonatal Genomes Project (2016–2021). Next-generation sequencing results and medical records were retrospectively evaluated to note the frequency of genetic diagnosis and the respective patient outcomes. Results: In total, 1795 patients were included. The human phenotype ontology term of atrial septal defect, patent ductus arteriosus and ventricular septal defect account for a large portion of the CHD subtype. Co-occurring extracardiac anomalies were observed in 35.1% of patients. 269 of the cases received genetic diagnoses that could explain the phenotype of CHDs, including 172 copy number variations and 97 pathogenic variants. The detection rate of trio-whole-exome sequencing was higher than clinical exome sequencing (21.8% vs 14.5%, p<0.05). Further follow-up analysis showed the genetic diagnostic rate was higher in the deceased group than in the surviving group (29.0% vs 11.9%, p<0.05). Conclusion: This is the largest cohort study to explore the genetic spectrum of patients with CHD in the NICU in China. Our findings may benefit future work on improving genetic screening and counselling for NICU patients with CHD.